MODERN INTERACTIVE METHODS IN TEACHING ENGLISH - Maftuna Khotamova Xoliqul qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: This article explores the effectiveness of modern interactive methods in teaching English as a second language. It investigates the impact of technology and student-centered approaches on language learning outcomes. The study includes a literature analysis, methods used, results obtained, a discussion of the findings, and concludes with suggestions for integrating these methods into English language classrooms.